POPULATION BEHAVIOR AS A CHALLENGE TOWARD RABIES CONTROL PROGRAM IN WEST SUMATRA - Salma Padri; Gindo M. Simanjuntak (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2002)
Rabies is geographically distributed in 8 provinces in Indonesia and its endemicity is quite related to the educational level of the dog owners. The more lower of the population education. it seems that the personal hygienic is worsen, and their dog immunization coverage is far less than 80% of dog population as recommended by World Health Organization, WHO. The objective of study is to determine the relationship between the dog owner family education level and their behavior toward rabies control program activity. This study is designed as Cross Sectional method and sampled by multistage procession, where the houshold sample was taken randomly from the high and the low endemicity of rabies. The dog owner was interviewed based on the prepared written questionnaire. The result of the study showed that the majority of the respondent population were low educational level where 73.0% in the cities and 49.0% in lhe villages not even passing the public school. Rabies transmission is known by 94.4% of the respondents respectively and 93.0% of them knew about rabies prevention by vaccination coverage among rabies transmitter animal was only 33.1 %. Educational level is significantly associated with tha dog owners behavior with p<0.05, (p:0.000). It is hoping, this study regarding the rabies control program will pay a valuable contribution in term of the dog oqwner knowledge improvement by public health education which will be given by the public health educator. Boar Hunter Clubs, local village key persons, or maybe by the religion leader.